Greek cultural influence and the revolutionary polices of Tiberius Gracchus - John F. OSSIER (Studia Historica: Historia Antigua, 2010)
RESUMEN: En el presente trabajo se aborda la importanciaque los referentes griegos puedieron tener en la reforma agraria de Tiberio Graco, como Diófanes de Mitileno o Blosio de Cumas, por encima de la escasa influencia de los círculos romanos. ABSTRACT: This study deals with importance that the Greek referents, such as Diophanes of Mytilene or Blossius of Cumae, may have had in the agricultural reforma of Tiberius Gracchus, greater than the sligt influence of Roman circles.